Prevalence and prevention of oesophageal injury during atrial fibrillation ablation: a systematic review and meta-analysis. Issue 1 (14th June 2018) - Ha, Francis J; Han, Hui-Chen; Sanders, Prashanthan; Teh, Andrew W; O'Donnell, David; Farouque, Omar; Lim, Han S
Abstract: Aims: Atrio-oesophageal fistula (AOF) is a potentially lethal complication of atrial fibrillation (AF) ablation. Many studies have evaluated the presence and prevention of endoscopically-detected oesophageal lesions (EDOL) as a proxy measure for risk of AOF. This systematic review and meta-analysis sought to determine the prevalence of EDOL and effectiveness of general preventive measures during AF ablation. Methods and results: We searched electronic databases for studies reporting prevalence or prevention of EDOL post-AF ablation. Pooled prevalence were reported with 95% confidence intervals (CI) while studies evaluating preventive measures including oesophageal temperature monitoring (OTM), esophageal manipulation and type of anaesthesia were analyzed descriptively or by random-effects modeling. Twenty-five studies were included in the analysis. Any and ulcerated EDOL pooled prevalence was 11% (95%CI, 6–15%) and 5% (95%CI, 3–7%), respectively. In six studies, there was no difference in EDOL with or without OTM (pooled OR 1.65, 95%CI, 0.22–12.55). There was no difference using a multi-sensor versus single-sensor OTM (one study) nor when using a deflectable probe (two studies). Oesophageal displacement was associated with significant instrumentation injury in one study. Two studies evaluating Oesophageal cooling showed conflicting results. General anaesthesia was associated with more EDOL than conscious sedation in two studies. Conclusion: The pooled prevalence of any and ulcerated EDOL post-ablation was 11% and 5%, but varied between studies. Techniques such as OTM and oesophageal displacement or cooling have not conclusively demonstrated a reduction in EDEL, while general anaesthesia may be associated with higher EDOL risk. Further randomized data are critically needed to validate and develop measures to prevent EDOL and AOF.